ECG Diagnosis in Clinical Practice - Peters, Nicholas. (Springer London, 2009)
The electrocardiogram (ECG) remains an essential tool in the diagnosis of cardiovascular disease. ECG Diagnosis in Clinical Practice emphasizes the importance of the technique in clinical practice rather than as an abstract analysis of lines on a strip of paper. It includes a large number of ECGs of greater difficulty level, and chapters in pediatric ECG and electrophysiology ensuring a comprehensive overall understanding of the subject. ECG Diagnosis in Clinical Practice has been written for those taking Board examinations, but the simplicity of approach and high quality images represent a valuable source of reference material for the more experienced cardiovascular physician.